2020
DOI: 10.3329/bjlr.v0i0.45444
|View full text |Cite
|
Sign up to set email alerts
|

A study on prevalence of ecto- and endo-parasitic infection of cattle at Savar, Dhaka

Abstract: A prevalence study was conducted to observe both ecto-and endo-parasitic (gastrointestinal) infection throughout one year surveillance. The study was conducted from July 2014 to June 2015 through Parasitology Laboratory, BLRI, Savar, Dhaka. The study considered age of cattle, season and type of parasitic infestation. In the study area total number of cattle population was 2000 in which 500 fecal and 200 ectoparasitic samples was collected considering three respective seasons like rainy, summer and winter. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 15 publications
2
0
0
Order By: Relevance
“…The highest incidence of parasites was observed in the rainy season (45.55%) followed by summer (32.12%) and winter (22.42%) which is shown in Table 2. These findings are well consistent with the observations of (Alim et al, 2012) and (Hassan et al, 2018). Lacking optimum moisture and temperature for the development of larvae in the pasture during the hot and cold season lowers and lowest the prevalence during summer and winter respectively.…”
Section: Resultssupporting
confidence: 93%
“…The highest incidence of parasites was observed in the rainy season (45.55%) followed by summer (32.12%) and winter (22.42%) which is shown in Table 2. These findings are well consistent with the observations of (Alim et al, 2012) and (Hassan et al, 2018). Lacking optimum moisture and temperature for the development of larvae in the pasture during the hot and cold season lowers and lowest the prevalence during summer and winter respectively.…”
Section: Resultssupporting
confidence: 93%
“…and ectoparasites (ticks, lice, and mites), resulting in aggressive parasitism. This conclusion validates Hassan et al [ 122 ] findings, which found that Bangladesh’s hot, humid environment favors the formation and survival of ectoparasites and endoparasites, as well as parasitic violence. The signs of an ecto-parasitic infection are visible to the naked eye.…”
Section: Discussionsupporting
confidence: 91%